Synthesis of controlled polymeric cross-linked coatings via iniferter polymerisation in the presence of tetraethyl thiuram disulphide chain terminator - Bossi, Alessandra; Whitcombe, Michael J.; Uludag, Yildiz; Fowler, S.; Chianella, Iva; Subrahmanyam, S.; Sanchez, I.; Piletsky, Sergey A. (Elsevier Science B.V., Amsterdam., 2010)
A “grafting from” approach has been used for controlled deposition of cross- linked polymers by living radical polymerisation. Borosilicate glass was modified with N,N-diethylaminodithiocarbamoylpropyl(trimethoxy)silane, in order to confine the iniferter reactive groups solely at its surface, then placed in solution with monomers and cross-linker. The polymerisation was initiated by UV irradiation. Formation of the cross-linked polymers was studied in terms of time course of the reaction, type of monomers incorporated and influence of oxygen. Grafted surfaces were characterised by AFM, FT-IR, ellipsometry and contact angle measurements. The ability to control the grafted layer improved dramatically when the chain terminator agent, N,N-N′,N′-tetraethyl thiuram disulphide (TED) was added. Upon irradiation TED increases the concentration of passive capping radicals and decreases the possibility of recombination of active macro-radicals, thus prolonging their lifetime. In the absence of TED the thickness of produced coatings was below 10 nm. TED added at different concentrations assisted in the formation of grafted layers of 10–130 nm thickness. Iniferter chemistry in the presence of TED can be used for growing nanometre-scale polymer layers on solid supports. It constitutes a robust general platform for controlled grafting and offer a general solution to address the needs of surface derivatisation in sensors t
Keywords: Surface-initiated polymers; Iniferter; Surface sensor; Grafting; Thiuram disulphide; Cross-linker